Treatment of Orbital Floor defects with Titanium Mesh in Zygomatic Complex Fractures - Tariq, Hasan; Firdous, Saadia; Umar, Mohammad; Haq, Usman Ul; Nishat, Mufassar; Irshad, Faiza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Outcome of treatment of orbital floor defects with titanium mesh in zygomatic complex fractures. Eye trauma results in significant aesthetic and functional problems. Rehabilitation necessitates a grasp of the orbit's altered structure and function, as well as the materials and procedures used in its restoration. Study design: Descriptive case series Study duration: 1 year.22 December 2018 to 21 December 2019. Study place: Allama Iqbal Teaching Hospital, Kh. Muhammad Safdar Medical College, Sialkot Results: This study was carried on 150 patients over a period of 6 months from January 1st 2013 to June 30th 2013 at the department of Oral & Maxillofacial Surgery PIMS Hospital Islamabad. 135/150(82.75%) patients were male and 15/150(17.24%) patients were female. The mean average age of the male patients was 30.02 years + 10.26 and the mean average age of the female patients was 29.90 years + 10.53. In our study 82.8% were males and 17.8 were females. Conclusion: The conclusion of study is titanium mesh isa better treatment option in management of complex orbito-zygomatico complex fractures, Diplopia is initially present but eventually resolve within 3 month.